2011
DOI: 10.3390/ijerph8041084
|View full text |Cite
|
Sign up to set email alerts
|

Applying Factor Analysis Combined with Kriging and Information Entropy Theory for Mapping and Evaluating the Stability of Groundwater Quality Variation in Taiwan

Abstract: In Taiwan many factors, whether geological parent materials, human activities, and climate change, can affect the groundwater quality and its stability. This work combines factor analysis and kriging with information entropy theory to interpret the stability of groundwater quality variation in Taiwan between 2005 and 2007. Groundwater quality demonstrated apparent differences between the northern and southern areas of Taiwan when divided by the Wu River. Approximately 52% of the monitoring wells in southern Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(28 citation statements)
references
References 37 publications
0
26
0
2
Order By: Relevance
“…The loading value of each trace element represents its contribution to the PC. HCA, on the other hand, is a multivariate statistical technique that can classify a large data set into some clusters or some smaller groups based on similarities defined as Euclidean distances among variables (Shyu et al 2011). HCA has been used to split water sample data into a small number of groups that have similar hydro-geochemical characteristics (Farnham et al 2003;Chen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The loading value of each trace element represents its contribution to the PC. HCA, on the other hand, is a multivariate statistical technique that can classify a large data set into some clusters or some smaller groups based on similarities defined as Euclidean distances among variables (Shyu et al 2011). HCA has been used to split water sample data into a small number of groups that have similar hydro-geochemical characteristics (Farnham et al 2003;Chen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It should be also noted that correlations among elements tend to decrease as the scales of study sites increase especially when groundwater chemistry varies markedly with scale. For example, Shyu et al (2011) reported that there are no significant correlations among heavy metals such as As, Cd, Cr, Cu, Pb, and Zn collected from 319 regional monitoring wells in Taiwan.…”
Section: Correlation Between Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shannon entropy, as a measure of information, including disorder, dispersion, and diversification, can reduce the uncertainty of indices by predicting the output of a probabilistic event [26]. It is considered to be an objective method to determine weights.…”
Section: Entropy Theorymentioning
confidence: 99%
“…WQIs, TOPSIS, and many other water quality assessment methods were improved by integrating the entropy [28,29]. The entropy weight can be calculated as follows [10,26,28].…”
Section: Entropy Theorymentioning
confidence: 99%